(untitled) (Scientific journal of the Fergana State University, 2023)
Surfactants are widely used to improve the quality of materials and regulate technological processes. The effectiveness of surfactants depends on the structure and composition of their molecules. Therefore, the study of the colloidal chemical properties of newly obtained surfactants is of great scientific and practical importance. The purpose of this work was to synthesize new surfactants based on phenol derivatives and to determine the relationship between their colloid-chemical properties. New surfactants were obtained based on the reaction of phenol with sulfuric acid and various alcohols. The synthesis of new surfactants was carried out by sulfurization of phenol with concentrated sulfuric acid in the presence of a catalyst, and the reaction product was esterified with primary alcohols. The surface activity and foaming abilities of the obtained new surfactants in aqueous solutions were studied.